Komposisi Serangga Kanopi di Kebun Apel di Poncokusumo, Malang dan Bumiaji, Batu - Amin Setyo Leksono; Bagyo Yanuwiadi; M Asmuni Hasyim; Frank Leonardo Apituley (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
This research abjective is to analyze the difference of abundance, diversity and composition of canopy insect in Poncokusumo and Bumiaji on blossoming and fruiting seasons. Insect compostions were observed by regular sampling using blue and yellow water pan trap. Water pan traps were suspended on apple stands at 2 m height. Sampling efforts was done by block system on 5 trees with 4 times collection, resulting 20 replications. Difference of mean was tested using general linear model analysis of variance. The canopy insect compositions between location were compared using Bray-Curtis similarity index. Overall, canopy insect diversity in two study sites was low. The abundance and diversity of canopy insect in Poncokusumo was higher than that in Bumiaji. The abundance and diversity of canopy insect in yellow traps was higher than that in blue traps. The effect of flowering phenology was significant on the overall abundance but not for the diversity. The effect of study locations on the abundance interacted with season. This meant there was a seasonal variation afecting location.